Ответ:
Объяснение:
Смотри
Ответ: 11a - 7b + 21 = 9
[tex]\displaystyle 11 a - 7 b + 21 = ? \\\\\\ \frac{4a - 5b + 6 }{5a - 4 b + 6 } = 3 \\\\\\ 4a -5b + 6 = 15 a - 12b + 18 \\\\ 11a - 7 b + 12 = 0 \\\\ 11a - 7b + 12 + 9 = 9 \\\\ \boxed{11a - 7b + 21 =9 }[/tex]
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
Объяснение:
Смотри
Ответ: 11a - 7b + 21 = 9
Объяснение:
[tex]\displaystyle 11 a - 7 b + 21 = ? \\\\\\ \frac{4a - 5b + 6 }{5a - 4 b + 6 } = 3 \\\\\\ 4a -5b + 6 = 15 a - 12b + 18 \\\\ 11a - 7 b + 12 = 0 \\\\ 11a - 7b + 12 + 9 = 9 \\\\ \boxed{11a - 7b + 21 =9 }[/tex]